Smoothening of wrinkles in CVD-grown hexagonal boron nitride films - Lin, Jinjun (2020)
Hexagonal boron nitride (h-BN) is an ideal substrate for two-dimensional (2D) materials because of its unique electrically insulating nature, atomic smoothness and low density of dangling bonds. Although mechanical exfoliation from bulk crystals produces the most pristine flakes, scalable fabrication of devices is still dependent on other more direct synthetic routes. To date, the most utilized method to synthesize large-area h-BN films is by chemical vapor deposition (CVD) using catalytic metal substrates. However, a major drawback for such synthetic films is the manifestation of thermally-induced wrinkles, which severely disrupt the smoothness of the h-BN films. Here, we provide a detailed characterization study of the microstructure of h-BN wrinkles and demonstrate an effective post-synthesis smoothening route by thermal annealing in air. The smoothened h-BN film showed an improved surface smoothness by up to 66% and resulted in a much cleaner surface due to the elimination of polymer residues with no substantial oxidative damage to the film. The unwrinkling effect is attributed to the hydroxylation of the h-BN film as well as the substrate surface, resulting in a reduction in adhesion energy at the interface. Dehydroxylation occurs over time under ambient conditions at room temperature and the smoothened film can be restored back with the intrinsic properties of h-BN. This work provides an efficient route to achieve smoother h-BN films, which are beneficial for high-performance 2D heterostructure devices.